2018
DOI: 10.1096/fj.201801068r
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone–dependent Kazal‐type serine protease inhibitor Greglin safeguards insect vitellogenesis and egg production

Abstract: In addition to preventing insect metamorphosis, juvenile hormone (JH) is known to stimulate aspects of insect reproduction. However, the molecular mechanisms of JH action in insect reproduction remain largely unknown. By reanalyzing the transcriptomic data from adults and other developmental stages of the migratory locust Locusta migratoria, we identified a gene coding for Kazal-type protease inhibitor, previously named Greglin. Greglin is specifically expressed in adult females and most abundant in the fat bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
(94 reference statements)
2
24
0
Order By: Relevance
“…We previously reported that hemolymph JH titers were undetectable at adult female eclosion, progressively elevated in previtellogenic phase, sharply increased in early vitellogenic stage, and rose to a peak in late vitellogenic stage (Fig. 1C) (Guo et al, 2019). Because adult female locusts started feeding 12 h post eclosion, the extremely low p-FoxO levels within 12 h after adult emergence might be primarily due to the absence of food intake.…”
Section: Jh Induces Foxo Dephosphorylation During Locust Vitellogenesismentioning
confidence: 72%
“…We previously reported that hemolymph JH titers were undetectable at adult female eclosion, progressively elevated in previtellogenic phase, sharply increased in early vitellogenic stage, and rose to a peak in late vitellogenic stage (Fig. 1C) (Guo et al, 2019). Because adult female locusts started feeding 12 h post eclosion, the extremely low p-FoxO levels within 12 h after adult emergence might be primarily due to the absence of food intake.…”
Section: Jh Induces Foxo Dephosphorylation During Locust Vitellogenesismentioning
confidence: 72%
“…Most recently a kazal-type serine protease inhibitor has been directly linked to oocyte development in the desert locust Schistocerca gregaria (Guo et al, 2019). A knock-down of the protein producing gene Greglin by RNAi caused extreme effects on reproduction, including; diminished oocyte production and maturation, a decline in the number of eggs produced and hatching success (Guo et al, 2019). Future work identifying the function of serine protease inhibitors in social insects is needed to better understand the function of parent-of-origin expression of these genes in both B. terrestris and A. mellifera .…”
Section: Discussionmentioning
confidence: 99%
“…2 (C and D), the levels of phosphorylated Na ϩ /K ϩ -ATPase ␣-subunit were significantly increased on day 2, reached peaks at 4 -7 days PAE, and then declined on day 8. As locust hemolymph JH titer is undetectable at eclosion but elevates significantly in the previtellogenic stage and rises to a peak during vitellogenesis (46,47), the elevation of Na ϩ /K ϩ -ATPase ␣-subunit phosphorylation appeared to correlate with its enhanced activity and the phase of increased JH titers.…”
Section: Jh Induces Pkc-mediated Phosphorylation and Activation Of Namentioning
confidence: 99%
“…The gregarious phase of migratory locusts was maintained under a light/dark photoperiod of 14 h/10 h and at 30 Ϯ 2°C as described previously (46). The diet included a continuous supply of wheat bran and fresh wheat seedlings provided once daily.…”
Section: Insects and Pharmaceutical Treatmentmentioning
confidence: 99%